The Cognitive-Affective Component of the Formation of a Social Work Specialist - Balakhtar, V; Balakhtar, K; Kuznietsova, Katheryna (My University, 2020)
The article presents the results of the study of the cognitive-affective component of the professional development of the social work personality. The purpose of the study is to determine the socio-psychological characteristics and the level of formation of the cognitive-affective sphere of social work specialists. According to the results of the research, there is an insufficient level of awareness and understanding of the peculiarities of the formation in the field of social work: most social work specialists understand the formation in the field of social work as a professional help to different categories of the population. Insufficient awareness of the system of indicators of formation of a specialist (professionally important qualities) has been established. The basic beliefs of specialists, the creative potential and its indicators, which turned out to be quite underdeveloped in social work specialists, are investigated. A high level of positive self-esteem was found in only about half of the subjects; less than half of those surveyed have low levels of psychological well-being, resulting inlow levels of empathy.
Keywords: social work specialist;understanding;experiences of positive feelings;psychological well-being.